Rationally Designed Protein Building Blocks for Programmable Hierarchical Architectures - Zhang, Wenbo; Mo, Shanshan; Liu, Mingwei; Liu, Lei; Yu, Lanlan; Wang, Chenxuan (Frontiers in Chemistry, 2020)
Diverse natural/artificial proteins have been used as building blocks to construct a variety of well-ordered nanoscale structures over the past couple of decades. Sophisticated protein self-assemblies have attracted great scientific interests due to their potential applications in disease diagnosis, illness treatment, biomechanics, bio-optics and bio-electronics, etc. This review outlines recent efforts directed to the creation of structurally defined protein assemblies including one-dimensional (1D) strings/rings/tubules, two-dimensional (2D) planar sheets and three-dimensional (3D) polyhedral scaffolds. We elucidate various innovative strategies for manipulating proteins to self-assemble into desired architectures. The emergent applications of protein assemblies as versatile platforms in medicine and material science with improved performances have also been discussed.